Limits on anomalous trilinear gauge couplings from WW→e+e-, WW→e±e, and WW→μ+μ- events from pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2006)
Limits are set on anomalous WWγ and WWZ trilinear gauge couplings using W+W-→e+νee-ν̄e, W+W-→e±νeμ νμ, and W+W-→μ+νμμ-ν̄μ events. The data set was collected by the Run II D0 detector at the Fermilab Tevatron Collider and corresponds to approximately 250pb-1 of integrated luminosity at s=1.96TeV. Under the assumption that the WWγ couplings are equal to the WWZ couplings and using a form factor scale of Λ=2.0TeV, the combined 95% C.L. one-dimensional coupling limits from all three channels are -0.32<Δκ<0.45 and -0.29<λ<0.30. © 2006 The American Physical Society.